Efeito da ativação ultrassônica de novos cimentos endodônticos na resistência de união e qualidade da obturação de canais radiculares - Padoin, Karine (2018)
The aim of this study was to investigate the effect of ultrasonic activation (UA) of three endodontic sealers on the bond strength to root dentin and root canal filling quality. Ninety-six bovine incisors were selected. After access and instrumentation, root canal filling was carried out using AH Plus (AP), Sealer Plus (SP) or Sealer Plus BC (BC), with or without UA (n=16/group). Then, two 1.5-mm slices were obtained from each root third. The first slice was subjected to push-out testing and failure mode analysis. The second slice was observed under a stereomicroscope for filling quality assessment, using a void score system. Data were analyzed by Kruskal-Wallis, Mann-Whitney and Friedman tests (α=0.05). Significant differences between sealers and types of activation were detected only in the apical third or when root thirds data were pooled. When no UA was applied, SP had higher bond strength than AP and BC. Also, SP presented lower void scores than BC. UA improved bond strength when BC was used, but did not affect the filling quality of any sealer. There were no significant differences between ultrasonically activated sealers, regarding bond strength and filling quality. Bond strength values were similar along the root depth, but there was a tendency to more voids in the apical third. The predominant failure mode was the mixed type. In conclusion, UA was effective in increasing the bond strength of the bioceramic sealer (BC), but did not improve its filling quality. Epoxy resin-based sealers (AP and SP) were not affected by UA.